The effects of wood chips and slash usage on skid trail sheet erosion caused by log skidding using a farm tractor : Učinci uporabe drvne sječke i šumskih drvnih ostataka na površinsku eroziju traktorskih vlaka uzrokovanu privlačenjem oblog drva poljoprivrednim traktorom - Turk, Yilmaz (Array, 2019)
This study investigated the sheet erosion that occurs as a result of log skidding operations using a farm tractor on skid trails and the use of wood chips and slash in order to minimize the soil loss. A total of four blocks (sample fields) were formed in four designated skid trails in the study area and three runoff plots were established in each block. One of the runoff plots was left empty as a control (CNT). Wood chips (C) was placed in the second plot and logging residue slash (S) in the third. A total of 108 water samples were taken from the test sites, 36 from each of the control, wood chips and slash plots. The water samples were brought to the laboratory and placed in an heating oven. After the runoff water was evaporated, the remaining sediment was weighed on a sensitive scale. The specified value was calculated according to the total amount of runoff accumulated in the storage tank and the total suspended sediment it carried. As a result, the amount of the average runoff in the CNT was determined as 6.32 mm/m2, in the C as 6.13 mm/m2 and in the S as 6.03 mm/m2. The average amount of suspended sediment transported in the CNT was found as 2.58 g m-2, in the C as 1.61 g m-2 and in the S as 2.13 g m-2. Therefore, the amount of soil loss in the control plots was about 1.2 times higher than in the slash plots and 1.6 times higher than in the wood chips plots. In this study, variance analysis results showed a statistically significant difference between the suspended sediment quantities carried from the plots (p <0.05). This study demonstrated that logging residues can be used to reduce the sheet erosion that occurs in skid trails after log extraction.